Synthesis and spectroscopic study of transition metal complexes of tridentate ligand formed by direct condensation of o-vanillin and 2-aminophenol: X-ray structural characterization of the zinc(II) complex - Gueye, Amadou; Tamboura, Farba Bouyagui; Planeix, Jean-Marc; Gruber, Nathalie; Gaye, Mohamed (European Journal of Chemistry, 2018)
The reactions of the Schiff base 2-((2-hydroxyphenylimino)methyl)-6-methoxyphenol (H2L), obtained by direct condensation of 2-aminophenol and 2-hydroxy-3-methoxybenzaldehyde, with some transition metal ions (Mn(II), Co(II), Ni(II), Cu(II) and Zn(II)) afforded complexes of general formulae [M2(L)2(solvent)x] (M: Mn, Co, Ni, Cu or Zn; Solvent: DMSO or H2O). These compounds were characterized by elemental analysis, UV-Vis, IR, 1H- and 13C-NMR spectroscopies, molar conductivity and room temperature magnetic measurements. The structure of zinc(II) complex has been determined by X-ray crystallography. Crystal data for C32H34N2O8S2Zn2 (M =769.47 g/mol): Orthorhombic, space group Pbca (no. 61), a = 16.3176(7) Å, b = 9.1247(3) Å, c = 21.8274(10) Å, V = 3250.0(2) Å3, Z = 4, T = 173(2) K, μ(MoKα) = 1.658 mm-1, Dcalc = 1.573 g/cm3, 28116 reflections measured (4.5° ≤ 2Θ ≤ 60.3°), 4457 unique (Rint = 0.0409, Rsigma = 0.0371) which were used in all calculations. The final R1 was 0.0307(0.0466) and wR2 was 0.0649 (0.0701) (all data). The coordination sphere of the Zn center is best described as a trigonal bipyramid.